Cold War: a Transnational Approach to a Global Heritage. (2nd January 2021) - Schofield, John; Cocroft, Wayne; Dobronovskaya, Marina
SUMMARY: Although within living memory, many countries now consider their surviving Cold War architecture as part of their heritage. It can even be a priority for heritage managers given that significant buildings are often suitable for reuse while extensive 'brownfield' sites such as airfields can be used for large-scale redevelopment. In a number of countries whose work we refer to here (notably the United Kingdom and elsewhere in Europe), agencies responsible for managing their country's heritage have approached this priority by creating national inventories of sites and buildings with a view to taking informed decisions on their future. This paper presents the argument that the wider international context of the Cold War provides a more appropriate (or additional, higher-level) framework for such decision making. Such a 'transnational' approach would allow the comparison of similar (e.g. European) sites not merely within national borders but across the full extent of their western NATO 1 deployment in Europe and North America. Taking this approach would also allow comparison with related sites in countries that formed part of the eastern-bloc Warsaw Pact. 2 After outlining some examples of how national agencies have approached their Cold War heritage, this paper presents the four stages of this transnational approach making provision for an improved understanding and management of Cold War heritage sites wherever they occur. With a specific focus on the direct comparison between England and Russia, and also referring to sites surviving elsewhere within the former NATO and Warsaw Pact regions, as well as the United States, we argue that this four-stage approach: provides new understandings of a complex archaeological and architectural record; gives fresh perspectives on significance; and (importantly in a time of geopolitical instability) does so in a spirit of cooperation and friendship.